The effect of simulation education on quality of the spinal column fixation - Fateme Moghimi; Mansour Dianati (Babol University of Medical Sciences, 2017)
BACKGROUND AND OBJECTIVE: Nursing in crisis consists of pre hospital specialized skills and cares for the survival of the injured, the lowering of physical and mental damage, safely transferring of injured and preventing of complication and worsening of their damages. Lack of nurse's skills may ne lead to problems aggravation and irreversible complications. Therefore, Obtaining Skill and experience in actual situations gradually is not enough rather, nurses should be educated step by step. Simulation in workshop is one of the best education ways. The purpose of this research is to investigate the effect of simulation education on quality of the spinal column fixation of simulated patient by nursing student of Kashan 1395. METHODS: This study was a Clinical trial that carried out on 34 nursing students of semesters 7 and 8 were selected and educated by simulation method. Instrument used in this study was a researcher structured checklist consisted of demographic information and evaluation list in order to valuation students skills including professional standards related to the method of the fixation of spinal column of the injured. After evaluation student's skills by the checklist, simulation was performed in workshop. Then, student's skills were evaluated by the checklist and data was analyzed by software SPSS, 22 version. FINDINGS: The study sample included 9 men (26.5%) and 25 women (73.5%) with average age of 22 years. The quality of effective fixation of spinal Column was 2.9% of cases in good level before intervention. However after the simulation education session this percentage was improved by 70.6% and there was significant difference between skills scores of nursing students before and after (P<0.001). CONCLUSION: Results showed that the simulation education was effective on the quality of the fixation of spinal column and improves nurse's skills.